Checking the adequacy of rainwater harvesting system for housing and landscaping - Mohammed, Thamer Ahmed; Megat Mohd Noor, Megat Johari; Ghazali, Abdul Halim (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
Rainwater harvesting has been the main source of water supply for potable and non-potable uses in the old days because the water conveyance systems were not used for water distribution and the method used for rainwater harvesting was simple and primary (rainwater was mostly collected from roofs and some was collected directly from the sky). Usage of the collected water volume from rainwater harvesting was direct and without any treatment. Presently, the water supply systems have improved but the demand is increasing due to the population growth, and development. Rainwater can be used for potable and non-potable uses. The potable uses include drinking, cooking, bathing and washing. Usually, the rainwater used for this purpose must be treated to remove the contaminants. Non-potable uses include flushing toilets, watering garden and washing floor where treatment of rainwater is not required for these purposes. The volume of rainwater collected from rainwater harvesting system varies from place to place and depends on weather. In the present study, a rainwater harvesting system was installed in the Faculty of Engineering, University Putra Malaysia, Malaysia. The system is composed of the catchment (roof), gutter, pipe, steel tank and treatment unit. From 20 different rain events, the collected volume of the rainwater from different events ranges between 0.17 m3 and 2 m3. The daily water consumption is monitored for one month and compared with the collected rainwater volume. The volume of collected rainwater is found to be adequate to meet the non-potable uses. In a tropical country like Malaysia it is easy to collect 2 m3 in a single rain while 10 m3 is collected annually in Zambia, Africa from a roof of almost of the same size. The rainwater harvesting can be used for landscaping and the computation made to determine the volumes of yield and consumption shows that rainwater is also adequate to meet the requirement for landscaping in rainy months.